Improve Writing Skills In Junior High Students Via Whatsapp Messenger - Lababa Lababa; Andi Asrifan; Muhammad Hanafi; Syarif Jasman Khalik; Saifullah Saifullah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
This study aims to evaluate the pros and cons of using WhatsApp Messenger to help students improve their writing abilities as well as to identify any gaps in the current literature. This study used a classroom action research methodology. To get the data, the researcher used tests, interviews, and observation. The researcher used the steps of data reduction, data display, and conclusion drafting when assessing the data. The study shows that using a scientific method helped students write recall texts more effectively. The proportion of scores for cycle I encompasses the rhetorical stages (67.50%), grammar (71.25%), vocabulary (66.25%), meaning clarity (67.50%), and relationship between concepts (63.75%). In cycle II, the percentage of scores encompasses vocabulary (76.25%), clarity of meaning (87.50%), grammar (78.75%), and link between ideas (81.25%). The students engaged in creative teaching and learning activities, showed interest in the teaching and learning processes, and openly expressed their opinions when associating and networking, according to this study. On the other hand, it also experienced difficulties with the teaching and learning procedures. The difficulties were that the majority of students lacked enthusiasm for studying WhatsApp. They must be directed to be disciplined in the classroom and encouraged to ask questions during the questioning phase.